2023
DOI: 10.3390/biom13040667
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Conformational Stability of the cl-Par-4 Tumor Suppressor via Site-Directed Mutagenesis

Abstract: Intrinsically disordered proteins play important roles in cell signaling, and dysregulation of these proteins is associated with several diseases. Prostate apoptosis response-4 (Par-4), an approximately 40 kilodalton proapoptotic tumor suppressor, is a predominantly intrinsically disordered protein whose downregulation has been observed in various cancers. The caspase-cleaved fragment of Par-4 (cl-Par-4) is active and plays a role in tumor suppression by inhibiting cell survival pathways. Here, we employed sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…We previously reported that at pH 4 with low salt, cl‐Par‐4 is highly helical and stable against aggregation (Clark et al, 2018 ; Pandey et al, 2023 ). Therefore, in an attempt to avoid the scattering phenomenon seen at pH 7, we repeated the 10:1 C:P binding studies at pH 4 with low salt (50 mM NaCl).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that at pH 4 with low salt, cl‐Par‐4 is highly helical and stable against aggregation (Clark et al, 2018 ; Pandey et al, 2023 ). Therefore, in an attempt to avoid the scattering phenomenon seen at pH 7, we repeated the 10:1 C:P binding studies at pH 4 with low salt (50 mM NaCl).…”
Section: Resultsmentioning
confidence: 99%